Next-generation mmWave WLAN: vision and key enabling technologies - Min FAN; Siyuan SHAO; Chao HE; Xiang WANG; Haiming WANG (物联网学报)
With the rapid development and wide applications of information and communication technologies, human production and life and social governance are evolving in the direction of digitizing, informatization, and intelligence.As one of the most widely applied wireless communication technologies, the wireless local area network (WLAN) needs to make further breakthroughs in the key performance such as data throughput, reliability, and latency and needs to add sensing functions and intelligence.The huge frequency resources of the millimeter wave (mmWave) band have injected new momentum into the development of WLAN.But the mmWave WLAN has also brought new technical challenges and requirements.Firstly, the WLAN development history was reviewed, and network structures, typical applications, development directions, and performance index requirements of WLAN in the future were summarized.Then, the characteristics of wireless channels in the mmWave band were given, and the new requirements and challenges for mmWave WLAN design were analyzed.Finally, some potential key technologies that may meet these challenges and requirements were discussed and prospected.